Synthesis of a novel ternary ZIF-8/GO/MgFe2O4 nanocomposite and its application in drug delivery - Saleheh Sanaei-Rad (Nature Portfolio, 2021)
Abstract In recent year, metal–organic frameworks (MOFs) have been displayed to be a category of promising drug delivery systems because of their crystalline structure, the potential of further functionality, and high porosity. In this research, graphene oxide was synthesized from pure graphite via hummer method and then MgFe2O4 nanoparticles was incorporated into the synthesized ZIF-8 metal–organic frameworks which followed with loading on the surfaces of graphene oxide. In continue, tetracycline as an antibiotic drug was loaded on the surfaces and the cavities of the prepared nanocomposite. The outcomes of this research revealed that 90% of the tetracycline was loaded on the synthesized ZIF-8/GO/MgFe2O4 nanostructure. Next, drug release was done at pH: 5 and pH: 7.4 within 3 days, resulting about 88% and 92% release of the tetracycline, respectively. With using different spectroscopic methods like X-ray crystallography (XRD), scanning electron microscope (SEM), energy-dispersive X-ray spectroscopy (EDX/Mapping), Fourier transform infrared (FTIR), thermalgravimetric analysis (TGA), and Brunauer–Emmett–Teller (BET), the structure of synthesized materials was confirmed. Furthermore, the antibiotic activity of tetracycline trapped into the ZIF-8/GO/MgFe2O4 was evaluated by agar-well diffusion method on both gram-positive (Staphylococcus aureus) and gram-negative (Escherichia coli) bacteria, which showed good antibacterial results.